The Effect of Religiosity and Maslahah Orientation on Halal Awareness, Satisfaction And Loyalty of Consumers of Halal Labeled Food - Irwan Habibi Hasibuan; Yuswar Z. Basri; Akhmad Affandi Mahfudz (GoAcademica Research & Publishing, 2021)
Halal food is one of the biggest issues that fill the academic and practical space in the sharia economy in the world today, so it is very important to be of more concern, especially in conducting sharia economic researches. Indonesia which is the largest Muslim-populated country in the world is the largest consumer of halal food in the world compared to other countries. In this study, consumers want to see halal labeled food that is influenced by religiosity and orientation over maslahah. In this study, the method used is the Structural equation model with the Amos Software tool. The sample used in this study was 176 Muslim students at the Mulia Cikarang Global Islamic Business Economics College.In this study, it was found that consumer loyalty is influenced by the satisfaction of consumers of halal-labeled foods. While the satisfaction of consumers of halal labeled food is influenced by religiosity and maslahah. This study also found that halal awareness is a variable that is significantly influenced by religiosity and not influenced by maslahah. So it is important to do more widespread ikhtiyar to build a more religious society to build halal awareness in the community. The findings are unique in this study where the direct influence of religiosity and orientation on maslahah is only significant to satisfaction and insignificant to loyalty. This means that the level of religiosity and orientation of existing maslahah in the new society can lead consumers of halal-labeled food to be satisfied consumers but not yet loyal consumers.